Challenges and Solutions for Improved Oral Health: Examples from Motivational Interviewing Trials. (April 2020) - Jamieson, L.M.; Garcia, R.I.; Sohn, W.; Albino, J.
Knowledge Transfer Statement: Irrespective of country, socially disadvantaged children experience greater levels of preventable dental disease than their more socially advantaged peers. Motivational interviewing (MI) is recognized as a potential intervention tool for reducing prevalence of child dental disease. The challenges of implementing MI in 4 trials involving socially vulnerable children are highlighted in this commentary, with some potential solutions offered.